Development of Chemically-Defined Artificial Diet for Menochilus Sexmaculatus Fabr. (Coleoptera: Coccinellidae) - H. Mustafa Majnu, Makhrani Sari Gintang (2002)
Studies on the nutritional requirements of the ladybird Menochilus sexmaculatus were conducted with the objective to develope a chemicallydefined artificial diet suitable for the growth and development of larvae and adults of M. sexmaculatus The formulated diet was presented following the paraffin coating droplet technique. A diet of 1:3 dilution (1 part ingredients and 3 parts water) was used for feeding the first instar larvae, while 1:1 dilution was for later instars and adults. Studies on yeast requirement showed that 7 g yeast hydrolysate improved survivorship, growth performance and longevity of M. sexmaculatus. As such this amount of yeast was mixed with 2 g casein hydrolysate, 5.5 g sucrose and 15 ml distilled water in a paraffin-vaseline ratio of 2:1 to form the basic diet. In the study on amino acid requirements, 02 g of each of the 1O-essential amino acids was added to the basic diet either together or separately. In a similar study on vitamin requirements, 02 g of different vitamins were added to the basic diet either together or separately. Results showed that M. sexmaculatus required methionine and histidine for the longest longevity, and pantothenic acid for the highest survivorship.